Елементи світобудови в ліриці Віри Вовк - Сіробаба, Микола; Sirobaba, Mykola (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття є спробою створення певного рівня детальності рисопису В. Вовк-поетки й умотування його в контекст української літератури другої половини минулого сторіччя й початку нинішнього шляхом окреслення особливостей художньої реалізації авторської концепції світобудови та висвітлення специфічних рис поетики, версифікації зразків лірики, складених у збірку «Ораторія хвали». The article is an attempt to recreate a certain level of detail portrait of the poet Vira Vovk in the context of Ukrainian literature of the second half of the last century and the beginning of present century by means of designation of the fictional features of the implementation of the author's conception of the world order and of elucidation of the specific features of her poetics, versification of poetry samples in Vovk's collection «Oratorio of praise». It was found that the focus of the poetry in this collection given to their meaning, its formal factors is often ignored or violated which is essentially in some cases because it made her poems nearly impossible to identify in the paradigm of systems of versification. The thematic spectrum of poetry in analyzed works is mainly the synthesis of pastoral poetry with philosophy, a man in these poems appears in most cases as a detached narrator-observator, who is endowed with empathy in some cases.
The Elements of the World Order in the Vira Vovk's Lyrics
Keywords: світ; світобудова; world; world order